2004
DOI: 10.1016/s1607-551x(09)70088-9
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell and Non‐Clear Cell Hepatocellular Carcinoma: A Case Report and Literature Review

Abstract: Clear cell hepatocellular carcinoma (HCC) is an uncommon variant of HCC. It is considered to have a better prognosis than non-clear cell HCC, but recent large studies show that there is some controversy. DNA image cytometry reveals diploid and non-diploid DNA content tumors that have different pleomorphisms and mitosis corresponding to different prognoses. Clear cell HCC is classified as focal or diffuse. Herein, we report a rare case of a 61-year-old male with two adjacent hyper- and hypoechoic hepatic nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Our study revealed that the age of patients diagnosed with PCCCL ranged from 52 to 76 years old and a large proportion of patients included in the overall cohort were white (65.6%, 275 of 419), which was roughly consistent to the results of the Jernigan et al study [20]. There was a male preponderance collectively, accounting for 64.0% of total patients, which was a little lower than 69.6% reported in a literature review [21].…”
Section: Discussionsupporting
confidence: 87%
“…Our study revealed that the age of patients diagnosed with PCCCL ranged from 52 to 76 years old and a large proportion of patients included in the overall cohort were white (65.6%, 275 of 419), which was roughly consistent to the results of the Jernigan et al study [20]. There was a male preponderance collectively, accounting for 64.0% of total patients, which was a little lower than 69.6% reported in a literature review [21].…”
Section: Discussionsupporting
confidence: 87%
“… 12 , 14 However, some other studies diagnosed PCCCL when the tumor contained >50% clear cells. 10 , 15 , 16 A recent study by Ji et al 16 suggested that cases with clear cells ≥70% had significantly longer survival than those with clear cells <70% in their research and another study of their own 10 stressed that the criteria for the diagnosis of PCCCL should be revised to the proportion of clear cells ≥75% and more studies should be designed to confirm the results of their research. Studies of this kind are quite limited and clinical prognostic features of PCCCL are not fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic accumulation of glycogen or lipid is related to the changes in metabolic pathways or metabolic defects within the cells [15]. Although the tumor cells of CCHCC are generally moderate or well differentiation, the incidence of tumor metastasis and recurrence after resection is similar to that of non-clear cell HCC (NCCHCC) [16, 17]. …”
Section: Introductionmentioning
confidence: 99%